Computational and Experimental Analysis of Conical Draft Tube’s Effect on Conical Basin of Gravitational Water Vortex Turbine - Acharya, Bishal; Chaulagain, Raj Kumar (Journal of Advanced College of Engineering and Management, 2023)
This paper presents an insight into the performance of the Gravitational Water Vortex Turbine (GWVT), a type of Ultra-Low Head (ULH) turbine, with and without the implementation of draft tube. Till date, no attention has been given on the effect of draft tube on GWVT. A model of GWVT along with a conical basin is developed on CATIA v5, and then subjected to a series of computational studies on ANSYS 2020R2. A similar setup is constructed in which a straight divergent draft tube is installed at the exit of the conical basin. The numerical approach suggested that maximum efficiency of the setup in the former case was 72.0% at 53 RPM whereas the efficiency in the latter case was 79.0% at 65 RPM. The increase in the efficiency was calculated to be 9.72%. This conclusion was validated through experimental verification conducted at Himalaya College of Engineering, Chyasal on a pre-fabricated test-rig of capacity 480 L, where the maximum efficiency of 69.4% and 64.5% were obtained with and without the installation of the draft tube respectively. Consequently, an increase of 7.59% in the efficiency of GWVT as an effect of draft tube was observed experimentally. It can be concluded that draft tube plays a vital role in the efficiency of the Gravitational Water Vortex Turbine.